Computer Vision - ECCV 2012: 12th European Conference on Computer Vision, Florence, Italy, October 7-13, 2012, Proceedings, Part III - Fitzgibbon, Andrew (Lecture notes in computer science, 2012)
Poster session -- Geometry: theory and application -- Learning and large-scale recognition -- Detection and attributes -- Actions and activities -- MRFs and early vision -- Geometry and recognition -- Lights, action.-Semantic segmentation.